On the welfare properties of the Lucas and Romer endogenous growth models - Sequeira, T. N.; Ferreira-Lopes, A. (Economics Bulletin, 2010)
We present results from quantitative exercises using the Lucas and Romer endogenous growth models, from which we calculate welfare losses from the distortions presented in the Romer model. Moreover, comparing the models to data, we show that an economy governed by the Romer model would attain a higher welfare than one governed by the Lucas model, contrary to what can be interpreted from some previous theoretical contributions.